Nonlinear properties and structural rearrangements in thermally poled niobium germanate glasses - Marcondes, Lia Mara [UNESP]; Orives, Juliane Resges [UNESP]; Adamitez, Frederic; Poirier, Gael Yves; Cardinal, Thierry; Dussauze, Marc; Nalin, Marcelo [UNESP] (Elsevier, 2024)
Second order nonlinear optical properties and structural rearrangements in GeO2–Na2O–Nb2O5 glasses were achieved by thermal poling. The effects of applied voltage as well as sodium and niobium contents on nonlinear optical (NLO)-active layer were investigated. Structural rearrangements in the anodic microlayer were investigated and occur due to sodium depletion promoting variation in bridging/non-bridging oxygen ratio and formation of a more polymerized network. Quantitative analysis of second harmonic generation signals confirm the electrooptical origin of the nonlinear optical response described by the electric-field-induced second harmonic model. χ(2) susceptibility values range from 0.42 to 0.76 pm/V depending on the niobium content. Lastly, the charge compensation mechanism with increasing applied voltage was described in detail. A progressive decrease in χ(2) for higher voltages was observed due to a greater poled thickness than expected by classical electrostatic models. In this case, the compensation mechanism occurs due to structural rearrangement, redox reactions, and motion of negative charges.
Keywords: Glass; Nonlinear optics; Thermal poling